‘Community health workers are unable to work because they don’t have supervisors’ - mid-level providers’ experiences of a CHW program in rural South Africa - Linnea Stansert Katzen; Mark Tomlinson; Christina Laurenzi; Ncumisa Waluwalu; Mary Jane Rotheram Borus; Sarah Skeen (James Cook University, 2023)
Introduction: The World Health Organization has called for more than 4 million community health workers (CHWs) globally; yet there are gaps in the evidence of CHWs' impact where studies have not had consistent results. South Africa is currently investing in CHW programs. However, there are significant concerns about the implementation and effectiveness of the program. Methods: We interviewed mid-level supervisors involved in eight rural clinics in a deeply rural South African municipality to identify the strengths and weaknesses of the CHW programs currently being implemented. Half of these clinics were part of a program providing enhanced supervision to CHWs, and the remainder were operating as usual. We hypothesized that stakeholders would provide valuable insights on how to improve the implementation of CHW programs. Fourteen interviews with supervisors from three levels of clinic and non-governmental organizations were conducted. Interviews were transcribed and translated from isiXhosa to English, and thematically analysed using ATLAS.ti. Results: Two overarching themes emerged: challenges at the national CHW program level (loss of political support, inadequacy of supervision and access to resources, human resource considerations); and experiences of the enhanced-supervision model provided (engagement and buy-in, link between CHW program and healthcare facilities, improvements through the intervention). Our findings suggest that CHWs operate largely unsupported, with limited access to training, equipment and supervision. The enhanced-supervision intervention appeared to mitigate some of these shortfalls. To make CHW programs efficient, we need to recruit CHWs based on social and administrative competence (rather than network referrals), provide improved higher quality training, provide more resources, especially equipment and transport, and ensure that CHWs receive supportive supervision that goes beyond simply administrative supervision. Furthermore, our findings suggest that the intervention in this study has somewhat mitigated these challenges through a package of supportive supervision and additional resources, highlighting the importance of stakeholder engagement and buy-in. It is clear that the governmental CHW program has many challenges - a number of which were temporarily mitigated by the intervention tested in this research's parent study. A list of recommendations for practice was developed from this work. First, contracts and reimbursements are important for CHW motivation, and are seen as essential prerequisites for CHW program success. Second, CHWs and other stakeholders must be involved in the design and implementation of the CHW program. Third, good-quality training and refresher trainings for CHWs is critical. Fourth, access to equipment such as scales is needed. Fifth, transport is critical in rural areas to access patients in remote areas. Lastly, supportive supervision was described as of upmost importance. Conclusion: CHWs have the potential to provide invaluable support in communities, and in rural communities in particular - but they need to operate in a functional supportive system. More resources need to be allocated to training, equipment and supportive supervision.